Insentif Pajak Dan Tingkat Kepercayaan: Pengaruhnya Terhadap Kepatuhan Wajib Pajak - Nik Amah; Candra Febrilyantri; Novi Dwi Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The research objective was to find out whether there was an effect of tax incentives on MSME taxpayer compliance during the COVID-19 pandemic with the level of trust in the government as a moderating variable. The sampling technique used is Accidental Sampling. The research sample are 100 respondents. Data collection through distributing questionnaires. Statistical testing to support Structural Equation Modeling (SEM) analysis using SmartPLS version 3.0 software. The results of the study document that tax incentives have a positive effect on MSME taxpayer compliance. The level of trust in the government is not able to moderate the effect of tax incentives on MSME taxpayer compliance.